Tin(IV) Complexes of Schiff Base Derived from Amino Acid: Synthesis and Characteristic Spectral Studies - Robina Aman; Garima Matela (Journal of Chemistry)
A new series of tin(IV) complexes of general formula [Sn(L-1)(Opri)2] (1), [Sn(HL-1)2(Opri)2] (2), [Sn(L-2)(Opri)2] (3), [Sn(HL-2)2(Opri)2] (4), (L is dianion of Schiff bases derived from the condensation of 2-hydroxy-1-naphthaldehyde with glycine (L-1) and Lβ-alanine (L-2)) was synthesized by reaction of tin(IV) tetraisopropoxide with the ligands, in appropriate stoichiometric ratios (1 : 1 and 1 : 2). This would result in the replacement of the isopropoxide group from the tin(IV) tetraisopropoxide and hydrogen(s) from ligand with the azeotropical removal of isopropanol. An attempt has been made to prove the structure of the resulting complexes on the basis of elemental analysis, IR, 1H nuclear magnetic resonance. The binding site of the ligand was identified by IR spectroscopic measurement. In these complexes, the tin(IV) centre is bonded to oxygen atom of the hydroxyl or carboxylate group. The spectra data suggest that the carboxylate group is coordinated to tin(IV) centre in monodentate manner.